BUDAYA ORGANISASI DENGAN KINERJA KARYAWAN CV BINTANG ABADI - Diah Ayu Fitri Hidayati; Sutarto Wijono (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to find out how the organizational culture of CV Bintang Abadi relates to employee performance. This study uses quantitative research techniques. 50 people participated in this study using the saturated sampling method, due to the limited number of samples less than 100 samples. To ensure that this research is a population study, it is best to involve all participants. The concept of organizational culture Koopmans and Beek (2014) to measure employee performance uses the Fey and Denison (2003) approach. To analyze the data used SPSS version 26.0. The research findings show that r = 0.450, p 0.05. The findings of this study indicate a relationship between organizational culture and performance.